Prevalence of Iron Deficiency and Iron-Deficiency Anemia in US Females Aged 12-21 Years, 2003-2020 - Weyand, Angela C; Chaitoff, Alexander; Freed, Gary L; Sholzberg, Michelle; Choi, Sung Won; McGann, Patrick T (JAMA : the journal of the American Medical Association, 2023)
This study examines prevalence of iron deficiency among females aged 12 to 21 years to inform future screening strategies for iron deficiency and iron-deficiency anemia.